Correlates of farmer’s background variables with their knowledge, adoption and technological gap regarding improved mushroom cultivation practices in Haryana - Kamal, Shwet; Makhija, V K; Singh, Surjeet; Shehrawat, P S (Mushroom Research, 2015)
Please see the full text